2017
DOI: 10.5961/jhes.2017.191
|View full text |Cite
|
Sign up to set email alerts
|

The use of discourse markers in the writings of turkish students of english as a foreign language: a corpus based study

Abstract: The aim of this study was to investigate the discourse markers used by 104 elementary-level prep class students studying at Namık Kemal University in Turkey. Students were required to write a paragraph with 80-100 words as part of their mid-term exam in the academic year of 2013-2014. A small-size corpus was constructed by using these writings. The corpus was analyzed via a software program called as AntConc 3.2.4. in order to find out the types and frequency of discourse markers. It was revealed that 180 disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Other studies support the use of the additive marker 'and' as well (Abal 2016;Altunay 2009;Bahaziq 2016;Dumlao and Wilang 2019;Kurtul 2011;Yin 2015Yin , Özdamar 2020. In Kurtul's (2011), Aysu's (2017 and Özdamar's (2020) studies, ve (and) was the most frequently used conjunction in Turkish. It is also interesting to see that ve conjunction was used more frequently in social sciences than in physical sciences (Sarıkaya 2020).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Other studies support the use of the additive marker 'and' as well (Abal 2016;Altunay 2009;Bahaziq 2016;Dumlao and Wilang 2019;Kurtul 2011;Yin 2015Yin , Özdamar 2020. In Kurtul's (2011), Aysu's (2017 and Özdamar's (2020) studies, ve (and) was the most frequently used conjunction in Turkish. It is also interesting to see that ve conjunction was used more frequently in social sciences than in physical sciences (Sarıkaya 2020).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Zorluel-Özer and Okan (2018) compared Turkish and native EFL teachers' lectures with regard to DMs. Since the use of DMs in writing is the concern of this paper, studies in written discourse (Al-khazraji, 2019;Aysu, 2017;Dumlao & Wilang, 2019;Feng, 2010;Kuzborska & Soden, 2018;Martinez, 2004;Povolna, 2012;Yunus & Haris, 2014) were summarized in detail below. Dumlao and Wilang (2019) examined 24 academic essays written by L1 and L2 English users, who are in a BA TESOL program, in terms of their DMs.…”
Section: Previous Studies On the Use Of Dmsmentioning
confidence: 99%
“…Numerous studies compared the use of DMs by native and non-native speakers of English (eg., Aysu, 2017;House, 2009). With the recognition of the significance of communicative competence, the number of studies about non-native speakers showed a notable increase over the last decades.…”
Section: Previous Research On Discourse Markersmentioning
confidence: 99%
“…Various studies have investigated the use of DMs or pragmatic markers by non-native speakers of English (Aijmer, 2011;Asık & Cephe, 2013;Aysu, 2017;Fung & Carter, 2007;Hellermann & Vergun, 2007;Liao, 2009). The variables which might affect the use of DMs have also been investigated mostly in some of these studies.…”
Section: Introductionmentioning
confidence: 99%